CD105 expression in cancer-associated fibroblasts: a biomarker for bone metastasis in early invasive ductal breast cancer patients - Giorello, María Belén; Martinez, Leandro Marcelo; Borzone, Francisco Raúl; Padin, María del Rosario; Mora, María Florencia; Sevic, Ina; Alaniz, Laura; Calcagno, María de Luján; García-Rivello, Hernán; Wernicke, Alejandra; Labovsky, Vivian; Chasseing, Norma Alejandra (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Bone metastasis is one of the causes that mainly decrease survival in patients with advanced breast cancer. Therefore, it is essential to find prognostic markers for the occurrence of this type of metastasis during the early stage of the disease. Currently, cancer-associated fibroblasts, which represent 80% of the fibroblasts present in the tumor microenvironment, are an interesting target for studying new biomarkers and developing alternative therapies. This study evaluated the prognostic significance of the CD105 expression in cancer-associated fibroblasts in early breast cancer patients. Methods: Immunohistochemistry was used to assess CD105 expression in invasive ductal breast carcinomas (n = 342), analyzing its association with clinical and pathological characteristics. Results: High CD105 expression in cancer-associated fibroblasts was associated with an increased risk of metastatic occurrence (p = 0.0003), particularly bone metastasis (p = 0.0005). Furthermore, high CD105 expression was associated with shorter metastasis-free survival, bone metastasis-free survival, and overall survival (p = 0.0002, 0.0006, and 0.0002, respectively). CD105 expression also constituted an independent prognostic factor for metastasis-free survival, bone metastasis-free survival, and overall survival (p = 0.0003, 0.0006, and 0.0001, respectively). Discussion: The high CD105 expression in cancer-associated fibroblasts is an independent prognostic marker for bone metastasis in early breast cancer patients. Therefore, the evaluation of CD105(+) CAFs could be crucial to stratify BCPs based on their individual risk profile for the development of BM, enhancing treatment strategies and outcomes.